Beliefs and strategies about urinary incontinence: a possible moderation role between symptoms and sexual function, and quality of life - Porto, Marta; Marôco, João; Mascarenhas, Teresa; Pimenta, Filipa (Frontiers in Psychology, 2023)
Background Urinary Incontinence (UI) has numerous repercussions in women’s lives, and it is underreported/underdiagnosed. Objective The present study aimed to understand: (1) the differences between women with and without urine loss regarding Quality of Life (QoL) and Sexual Function (SF); (2) the possible moderation role of UI-related beliefs and strategies on the relationship between UI-symptom severity and SF and QoL, in women with UI. Methods Cross-sectional Design. Participants: Primary aim: Overall, 2,578 women aged 40–65 (Mage = 49.94, DPage = 6.76) were collected online. Secondary aim: 1,538 women who self-reported having urine loss occasionally/frequently (Mage = 50.19, DPage = 6.58). All data analyses were done with IBM SPSS Statistics and R statistical system 4.0 through RStudio. Statistical Path analysis was performed with the lavaan package to study the hypothetical association and moderating effects between the variables. Results Primary aim: women without UI had a better SF [t(2576) = 3.13, p = 0.002; 95% C.I., 0.18 to 0.80] and QoL [t(2576) = 7.71, p < 0.001; 95% C.I., 3.14 to 5.28] than their counterparts with UI. Secondary aim: UI-related coping strategies attenuated the impact of UI-symptom severity on SF(β = −0.07; p = 0.041); the more dysfunctional the UI-related beliefs were, the poorer QoL was (β = −0.06; p = 0.031); the more frequent the UI-related hiding/defensive strategies were, the poorer QoL was (β = −0.26; p < 0.001). Discussion Limitations: online data collection, which thwarted the clarification of participants, if needed; absence of a UI medical diagnosis (only self-reported measures were used). Strengths and practical implications: (i) the crucial role of UI-related beliefs and strategies in the QoL of women with UI; (ii) the impact that UI-concealing/defensive strategies have in attenuating the impact of UI-symptom severity on SF, which might be perceived as a short-term benefit and hence contribute to maintaining the UI condition and constitute a barrier to help-seeking, (iii) impact of UI-symptom severity on QoL and SF (including a comparison group entailing women without UI, which is scarcely used); and (iv) the use of gold-standard and psychometrically robust instruments. Conclusion Changing dysfunctional UI-related beliefs and strategies in clinical settings may improve the QoL; UI-concealing strategies may reinforce themselves by immediate effects on SF, but are not functional in the long term.